Work-School Conflict and Working Students - The Impact of Type of Employment on Academic Outcomes - Jardim, Jessica-Jo (Organisational Psychology, 2021)
The sustainable development of working students in tertiary education institutions is important for student retention and institutional success. As the number of working students is on the rise, it is imperative that the needs of working students are well-recognized to ensure academic satisfaction and engagement. As these students encompass the role of both an employee and a student, inter-role conflict is experienced when pressures from the workplace disrupt academic responsibilities and influence academic outcomes. Therefore, the aim of the present study was to examine the impact of type of employment (part-time employment and full-time employment) on university outcomes, namely academic satisfaction and academic engagement of working students. The study proposed that those working students in part-time employment would on average experience less work-school conflict, more academic satisfaction and more academic engagement than those working students in full-time employment. The study implemented a secondary crosssectional descriptive design, whereby secondary data was used. The study's sample consisted of working students (n = 482). Independent samples t-tests and mediation analyses were conducted to analyse the study's hypotheses. A significant difference was found between those working students who participated in part-time and full-time employment, in terms of their work-school conflict and academic satisfaction. However, no significant difference was found for the academic engagement outcome. The analyses revealed that work-school conflict mediated the relationship between type of employment and academic satisfaction, however mediation effects were not found between type of employment and academic engagement. The findings of the study have theoretical contributions and practical implications for university intuitions and researchers. Lastly, research contributions and suggestions for future research are presented.